SALMONELLA-PARATYPHI A OSTEOMYELITIS IN A PATIENT WITH RHEUMATOID-ARTHRITIS - Wordsworth, B; Bedford, A; Wood, J (1982)
A case of Salmonella paratyphi A osteomyelitis is reported. Complete recovery occurred following immobilization and prolonged treatment with appropriate antibiotics.